Type 3 Deiodinase: Role in Cancer Growth, Stemness, and Metabolism - Ciavardelli, Domenico; Bellomo, Maria; Crescimanno, Caterina; Vella, Veronica (Frontiers in Endocrinology, 2014)
Deiodinases are selenoenzymes that catalyze thyroid hormones (THs) activation (type 1 and type 2, D1 and D2 respectively) or inactivation (type 3, D3). THs are essential for proper body development and cellular differentiation. Their intra- and extra-cellular concentrations are tightly regulated by deiodinases with a pre-receptorial control thus generating active or inactive form of THs. Changes in deiodinases expression are anatomically and temporally regulated and influence the downstream TH signaling. D3 overexpression is a feature of proliferative tissues such as embryo or cancer tissues. The enhanced TH degradation by D3 induces a local hypothyroidism thus inhibiting THs transcriptional activity. Of note, overexpression of D3 is a feature of several highly proliferative cancers. In this paper we review recent advances in the role of D3 in cancer growth, stemness and metabolic phenotype. In particular we focus on the main signalling pathways that result in the overexpression of D3 in cancer cells and are known to be relevant to cancer development, progression, and recurrence. We also discuss the potential role of D3 in cancer stem cells metabolic phenotype, an emerging topic in cancer research.